Heterodoxia e inquisición en Querétaro - Ramírez Leyva, Edelmira; Suárez Escobar, Marcela; Ríos de la Torre, Guadalupe; Pappe Willenegger, Silvia; Buelna Serrano, María Elvira, coord. (Universidad Autónoma Metropolitana, Unidad Azcapotzalco, División de Ciencias Sociales y Humanidades, Departamento de Humanidades; Universidad Autónoma de Querétaro, 2014)
1 archivo PDF (219 páginas)